Characteristics of Polycystic Ovarian Syndrome in Sub-fertile Woman Attending to GOPD in ShSMCH (Journal of Shaheed Suhrawardy Medical College, 2019)
Background: Polycystic ovarian syndrome (PCOS) is a condition characterized by menstrual abnormalities (oligo/amenorrhea) and clinical or biochemical features of hyperandrogenism and may manifest at any age. It is a common cause of female subfertility. All the dimensions of PCOS have not been yet completely explored.Methods: It was a cross sectional comparative study carried out at-GOPD of Shaheed Suhrawardy Medical College & Hospital from January, 2016 to December 2016 on 162 subfertile women. Among them 54 were PCOS group and 108 were non PCOS group. PCOS was diagnosed by (Rotterdam criteria 2003) (i) Oligo or anovulation (ii) hyperandrogenism (iii) Polycystic ovaries. Study was done to evaluate and compare the demographic characteristics, clinical, biochemical and ultrasoundgraphic features of sub-fertile women with and without PCOS.Results: A total of 162 sub-fertile women aged 16-36 years. Mean age was 29.5±5.4. There were significant differences between the two groups in terms of (oligo/amenorrhea), hirsutism, WHR and ovarian ultrasound features. There were no significant differences between two groups in correlations between the level of obesity with the incidence of anovulation, hyperandrogenism or with hormonal features.Conclusion: PCOS is one of the important factors causing Infertility. It is an ill-defined symptom complex needed due attention. There is a need to increase awareness regarding. The clinical features of PCOS are heterogenous thus can be investigated accordingly of selection of appropriate treatment modality.J Shaheed Suhrawardy Med Coll, June 2019, Vol.11(1); 17-23